Las deficientes participaciones de las socias del comedor "pazs y esperanza" del asentamiento humano los jardines, distrito de pueblo nuevo, provincia de chepén, durante el período octubre 2012 - febrero 2013. - Cáceda Quiroz, Estéfany Lizet (2013)
The formless present of thesis demonstrates which are the social factors that influence in deficient participations of the socias of the dining room " Peace and Hope " of the Accession I humanize The Gardens, district of New People, Chepén's Province during the period in October 2012 - February 2013, for what in this social institution the inadequate interpersonal relations and the low level of communication for the teamwork are which limit the suitable functioning in the organization and in the personal and social well-being of the socias. When we refer to the inadequate interpersonal relations we are meaning that the socias of the dining room " Peace and Hope ", they carry to the breaches of functions, the low assistances to meetings and to the scanty participation in the activities summoned by the board of directors; likewise relating to the low level of communication for the teamwork we us are refiriendo to what they produce that the socias of the dining room " Peace and Hope " and the board of directors they have absence of leadership impeding the organization between the socias.